Contemporary incidence and risk factors of post transplant Erythrocytosis in deceased donor kidney transplantation - Sami Alasfar; Isaac E. Hall; Sherry G. Mansour; Yaqi Jia; Heather R. Thiessen-Philbrook; Francis L. Weng; Pooja Singh; Bernd Schröppel; Thangamani Muthukumar; Sumit Mohan; Rubab F. Malik; Meera N. Harhay; et al. (BMC Nephrology, 2021)
Abstract Background Post-Transplant erythrocytosis (PTE) has not been studied in large recent cohorts. In this study, we evaluated the incidence, risk factors, and outcome of PTE with current transplant practices using the present World Health Organization criteria to define erythrocytosis. We also tested the hypothesis that the risk of PTE is greater with higher-quality kidneys. Methods We utilized the Deceased Donor Study which is an ongoing, multicenter, observational study of deceased donors and their kidney recipients that were transplanted between 2010 and 2013 across 13 centers. Eryrthocytosis is defined by hemoglobin> 16.5 g/dL in men and> 16 g/dL in women. Kidney quality is measured by Kidney Donor Profile Index (KDPI). Results Of the 1123 recipients qualified to be in this study, PTE was observed at a median of 18 months in 75 (6.6%) recipients. Compared to recipients without PTE, those with PTE were younger [mean 48±11 vs 54±13 years, p < 0.001], more likely to have polycystic kidney disease [17% vs 6%, p < 0.001], have received kidneys from younger donors [36 ±13 vs 41±15 years], and be on RAAS inhibitors [35% vs 22%, p < 0.001]. Recipients with PTE were less likely to have received kidneys from donors with hypertension [16% vs 32%, p = 0.004], diabetes [1% vs 11%, p = 0.008], and cerebrovascular event (24% vs 36%, p = 0.036). Higher KDPI was associated with decreased PTE risk [HR 0.98 (95% CI: 0.97–0.99)]. Over 60 months of follow-up, only 17 (36%) recipients had sustained PTE. There was no association between PTE and graft failure or mortality, Conclusions The incidence of PTE was low in our study and PTE resolved in majority of patients. Lower KDPI increases risk of PTE. The underutilization of RAAS inhibitors in PTE patients raises the possibility of under-recognition of this phenomenon and should be explored in future studies.